Genome-wide identification of Cymbidium sinense WRKY gene family and the importance of its Group III members in response to abiotic stress - Wei, Yong-Lu; Jin, Jian-Peng; Liang, Di; Gao, Jie; Li, Jie; Xie, Qi; Lu, Chu-Qiao; Yang, Feng-Xi; Zhu, Gen-Fa (Frontiers in Plant Science, 2022)
Transcription factors (TFs) of the WRKY family play pivotal roles in defense responses and secondary metabolism of plants. Although WRKY TFs have been widely characterized in many plants, a genome-wide analysis of the WRKY gene family is lacking in Cymbidium sinense. In the present study, we identified 64 C. sinense WRKY (CsWRKY) TFs, which were further classified into eight subgroups. Chromosomal distribution of CsWRKYs indicated that most genes were dispersed on 16 chromosomes, especially enriched on Chromosome 2. Syntenic analysis revealed that 13 (20.31%) genes were derived from either segmental duplication events, and 17 orthologous gene pairs were identified between Arabidopsis thaliana WRKY (AtWRKY) and CsWRKY genes. Moreover, 55 of the 64 CsWRKYs were detectable in different plant tissues in response to exposure to plant hormones. Among them, Group III members were strongly induced in response to various hormone treatments, indicating their potential essential roles in hormone signaling. We subsequently analyzed the function of CsWRKY18 in Group III. The CsWRKY18 was localized in the nucleus. The constitutive expression of CsWRKY18 in Arabidopsis resulted in enhanced sensitivity to ABA-mediated seed germination and root growth and elevated plant tolerance to abiotic stress within the ABA-dependent pathway. Overall, our study represented the first genome-wide characterization and functional analysis of WRKY TFs in C. sinense, which could provide valuable information about the evolution and functional characterization of CsWRKY genes.